Evaluation of antidiabetic and antioxidant properties of brucea javanica seed - Ablat, Abdulwali; Mohamad, Jamaludin; Awang, Khalijah; Shilpi, Jamil A.; Arya, Aditya (Hindawi Publishing Corporation, 2014)
The ethanol extract of B. javanica seed was fractionated with solvents of different polarities and tested for antioxidant activities by several assays including DPPH radical scavenging activity, ferric reducing antioxidant power (FRAP), ferrous ion chelating activity (FCA), and nitric oxide radical scavenging activity (NORSA) along with their polyphenolic contents. Antidiabetic activity was evaluated both in vitro and in vivo using a glycogen phosphorylase α (GPα) inhibition assay and oral glucose tolerance test (OGTT) in nondiabetic rats. The ethyl acetate fraction (EAF), rich in tannin, exhibited the strongest antioxidant activities to DPPH, FRAP, and NORSA, except for FCA. The EAF also exerted a dose-depended inhibition of GPα (IC50 = 0.75 mg/ml). Further evaluation of hypoglycemic effect on OGGT indicated that rats treated with EAF (125 mg/kg bw) showed a 39.91% decrease (P < 0.05) in blood glucose levels at 30 min, and continuous fall (P < 0.05) of 28.89% and 20.29% was observed in the following hours (60 and 90 min) compared to the normal control during OGTT. The EAF was applied to polyamide column chromatography, and the resulting tannin-free fraction was tested for both GPα inhibition and antioxidant (DPPH only) activity. The GPα inhibitory activity was retained, while antioxidant activity was lost (4.6-fold) after tannin removal. These results concluded that the GPα inhibitory activity initially detected was primarily due to the compounds other than tannins, whereas antioxidant activity was mainly due to the tannins.